2005
DOI: 10.1515/mamm.2005.016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of grouping patterns and social segregation in feral goats (Capra hircus) on the Isle of Rum, NW Scotland

Abstract: Miller D. 2005. -Dynamics of grouping patterns and social segregation in feral goats ( Capra hircus) on the Isle of Rum, NW Scotland. Mammalia 69 (2) : 185-199. ABSTRACTWe investigated group size, grouping patterns and sexual segregation in feral goats on the Isle of Rum (NW Scotland)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 53 publications
5
43
0
2
Order By: Relevance
“…In this study, feral goats showed variations in herd size across the year, as reported previously by Shi et al (2005) and Suances (2010), being greater in summer and winter. Gregariousness is a condition that allows information to be transmitted within herds (Wilson et al, 1975), a condition quite frequently reported in feral goats.…”
Section: Structure Of Herdssupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, feral goats showed variations in herd size across the year, as reported previously by Shi et al (2005) and Suances (2010), being greater in summer and winter. Gregariousness is a condition that allows information to be transmitted within herds (Wilson et al, 1975), a condition quite frequently reported in feral goats.…”
Section: Structure Of Herdssupporting
confidence: 87%
“…The structure of herds observed in both goat ecotypes in the Serra de Tramuntana of Majorca follows the pattern reported for other feral goat populations (Parkes, 1984;Shi et al, 2005), as well as the one usually observed in other wild goat populations (Shaller, 1977). The basic social unit is generally an adult female and her offspring, which associate with similar groups in a given area (O'Brien, 1988).…”
Section: Structure Of Herdssupporting
confidence: 83%
“…The feral goats sometimes feed alone but more usually do so in loosely associated groups whose sizes range from 2-51 (with two to three being the modal group size) (Shi et al 2005). The composition and membership of the groups are very changeable, with individuals joining or leaving frequently as the animals forage across the landscape.…”
Section: Study Area and Populationmentioning
confidence: 99%
“…While feral goats (Capra hircus) are no exception, the level of segregation in the population inhabiting the Isle of Rum is modest and rather unstable (Shi et al 2005), with adult males and females forming mixed groups even outside of breeding season. However, mixed-sex foraging groups are especially common during and after the rut (August through the autumn months) when individual males may spend days at a time with a group of females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation